Study of association of TGF-ß1 polymorphism with breast density in a tertiary medical center of Malaysia - Wan Rohani Wan Taib; Amiratul Athirah S; Nasriah A; Mohaslida M; Tengku Fatimah Murniwati TM; Norhasiza MJ; Husbani Mar; Elinah A (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Early detection of breast cancer risk by screening tools such as mammography can reduces the cost of treatment management and the prognosis of the disease. The level of breast density of in mammogram is one of the potential cofounder factor for breast cancer risk. The development of mammary epithelial cells is determined by the genetic factor. Transforming growth factor-beta (TGF-ß) gene involves in the regulation of cell proliferation and cell division. This study aimed to assess the association of TGF-ß1 polymorphisms with breast density among women who underwent breast screening using mammogram. The detection of genotypes for three polymorphisms of TGF-ß1 assigned as rs1800469, rs1800470 and rs4803455 were performed using PCR-RFLP technique. The allele and genotype frequencies were calculated for control group that consists of BIRADS 1 and BIRADS 2 class whilst case group consisted of BIRADS 3 and BIRADS 4 class. Two polymorphisms (rs1800469 and rs1800470) yielded a significant association with breast density with p value of 0.004 and 0.003, respectively. However, the third polymorphism, rs4803455 did not yield a significant association (p value=0.090). Haplotype association analysis might suggest the haplotype GAA conferred susceptibility (p value= 0.02, OR=2.21[1.07-4.55]) rather than haplotype AAC predispose a protective effect (p value=0.004, OR=0.40[0.21-0.77]) to breast density development. This preliminary data on single and haplotype association might reveal the association of polymorphisms of TGF-ß1 with breast density and give an insight on the role of polymorphism in predisposing to breast density development.